Multiculturalism policy and security in Europe - Irena Valer'evna Lebedeva (Современная наука и инновации, 2022)
The article is devoted to the policy of multiculturalism in contemporary Europe and the PEGIDA (progressive Europeans against the Islamization of the West). The author notes the situation in Europe today because of the problems of the migrants integration into the host community, reveals some specificity inherent in individual countries and the reaction of citizens to their government’s recognition of insolvency policy of multiculturalism. A misunderstanding between the migrants and their host community, the desire to preserve their own identity, not dissolve in the “melting pot” of cultural diversity, constitute the research question of the article. The desire to maintain intercultural interaction and balance between the own and the stranger in a multicultural and multiethnic society are the basis of European cultural security today. The article is written with the financial support of Russian Foundation for Humanities: project № 15-33-11172 “Cultural Security in Heterotopia”